PENINGKATAN KEAKTIFAN SISWA DALAM PEMBELAJARAN IPA MELALUI PENDEKATAN COOPERATIVE TIPE NUMBERED HEAD TOGETHER PADA SISWA KELAS V SD NEGERI 2 BUWARAN MAYONG JEPARA (Improving Students’ Activity in Learning Science through Cooperative Approach: Type Numb - Musfirotun, Musfirotun (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
The backgrounds of the research were the lack of studentsÃ¢â‚¬â„¢ activity in learning science, studentsÃ¢â‚¬â„¢ dissatisfactory achievement, and the lack of learning media. Numbered Head Together cooperative approach (NHT) model was used to overcome those problems. Subject of the research were the students of year V Buwaran 2 State Primary School. This belonged to classroom action research with steps ofÃ‚Â  planning, acting, observing, and reflecting. The research results showed that obtained average score on studentsÃ¢â‚¬â„¢ activity tended to improve significantly. At the first cycle, the average score was 59%, second cycle was 79%, and the third one was 90%. The next result was that teacherÃ¢â‚¬â„¢s activity also improved. The average score in sequence was 78% at cycle 1, 88% at cycle 2, and 95% at the last cycle. The third result of the research was that studentsÃ¢â‚¬â„¢ achievement also improved. They got average score 60% at cycle one, 75% at cycle two and 95% at the last one. So that based the data, it could be concluded that NHT Cooperative approachcould improve activity of the fifth grade students of Buwaran 2 State Primary School. Keywords: studentsÃ¢â‚¬â„¢ activity in learning science Ã‚Â